2020
DOI: 10.1021/acs.inorgchem.0c00742
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne Functionalization of a Photoactivated Ruthenium Polypyridyl Complex for Click-Enabled Serum Albumin Interaction Studies

Abstract: Studying metal-protein interactions is key for understanding the fate of metallodrugs in biological systems. When a metal complex is not emissive and too weakly bound for mass spectrometry analysis, however, it may become challenging to study such interactions. In this work a synthetic procedure was developed for the alkyne functionalization of a photolabile ruthenium polypyridyl complex, [Ru­(tpy)­(bpy)­(Hmte)]­(PF6)2, where tpy = 2,2′:6′,2′′-terpyridine, bpy = 2,2′-bipyridine, and Hmte = 2-(methylthio)­ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“… a In water b In methanol- d 4 ;[ 39 ] c Data taken from Bahreman et al [ 18 ] d Data Busemann et al [ 40 ] …”
Section: Resultsmentioning
confidence: 99%
“… a In water b In methanol- d 4 ;[ 39 ] c Data taken from Bahreman et al [ 18 ] d Data Busemann et al [ 40 ] …”
Section: Resultsmentioning
confidence: 99%
“…It is advantageous to study serum albumin, as the limited number of binding sites with high specificity plays a pivotal role in the transportation and delivery of different endogenous and exogenous species . Bovine serum albumin (BSA), having a 76% sequence homology for human serum albumins (HSA), has been broadly studied, as it is the most abundant model protein of blood plasma. , From literature reports, it has been observed that vanadium complexes showing higher DNA and protein binding ability exhibited better cytotoxicity, and so the assessment of this ability is an important aspect prior to anticancer studies, ,,, but the involvement of several other mechanisms of cellular activity may also be possible. In some reports, the cellular cytotoxicity activity of transition-metal complexes (V and Cu) follows a mechanism of action different from DNA and protein interactions. Possibly, the increased electron density in the aromatic ring systems, aqueous solubility, membrane permeability, or specific hydrophobic interactions in target binding pockets lead to an increase in cytotoxicity. , In this context, due to hydrophobicity, enhancement in the bioavailability of a drug by its internalization to the target cells and ability to reach the site of action is another point of interest. , Thus, in this work, we have sought to correlate the behavior of complexes in aqueous stability, hydrophobicity, DNA/protein interactions related to their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…53 Bovine serum albumin (BSA), having a 76% sequence homology for human serum albumins (HSA), has been broadly studied, as it is the most abundant model protein of blood plasma. 53,54 From literature reports, it has been observed that vanadium complexes showing higher DNA and protein binding ability exhibited better cytotoxicity, and so the assessment of this ability is an important aspect prior to anticancer studies, 17,33,36,55−57 but the involvement of several other mechanisms of cellular activity may also be possible. 58−60 In some reports, the cellular cytotoxicity activity of transitionmetal complexes (V and Cu) follows a mechanism of action different from DNA and protein interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, the preparation of terpyridine derivatives that contain a functionalized pyrrole is of interest in the fields of both organic synthesis and material science. This article describes how pyrrole-containing terpyridine 1 was obtained as an unexpected product during attempts to prepare compound 2 (Figure 1), which features an alkyne chain for possible future functionalization [15].…”
Section: Introductionmentioning
confidence: 99%